2007
DOI: 10.1111/j.1365-2249.2007.03425.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung macrophages from bacille Calmette–Guérin-vaccinated guinea pigs suppress T cell proliferation but restrict intracellular growth ofM. tuberculosisafter recombinant guinea pig interferon-γ activation

Abstract: SummaryThe guinea pig model of low-dose pulmonary tuberculosis has been used to study the pathogenesis of infection as well as the mechanisms of bacille Calmette-Guérin (BCG) vaccine-induced resistance. We investigated the function of lung cells from naive and BCG-vaccinated guinea pigs after enzymatic digestion of lung tissue with collagenase and DNase I. The total lung digest cells proliferated poorly to purified protein derivative (PPD) but comparatively better to ConA as assessed by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…Other supporting ex vivo studies indicate that AMs from BCG-vaccinated guinea pigs challenged with M.tb express significantly less IL-10 and more IL-12p40, compared to unvaccinated controls (45). This same study reported an elevated expression of MHC II on peritoneal macrophages from BCG-vaccinated guinea pigs (45).…”
Section: Innate Immune Responses To Bcg Vaccinationmentioning
confidence: 96%
See 1 more Smart Citation
“…Other supporting ex vivo studies indicate that AMs from BCG-vaccinated guinea pigs challenged with M.tb express significantly less IL-10 and more IL-12p40, compared to unvaccinated controls (45). This same study reported an elevated expression of MHC II on peritoneal macrophages from BCG-vaccinated guinea pigs (45).…”
Section: Innate Immune Responses To Bcg Vaccinationmentioning
confidence: 96%
“…Other supporting ex vivo studies indicate that AMs from BCG-vaccinated guinea pigs challenged with M.tb express significantly less IL-10 and more IL-12p40, compared to unvaccinated controls (45). This same study reported an elevated expression of MHC II on peritoneal macrophages from BCG-vaccinated guinea pigs (45). Thus, based on our current understanding of the requirements for mycobacterial immunity; immunity induced by the BCG vaccine results in responses to M.tb at the early phase of infection that directly impact macrophage function.…”
Section: Innate Immune Responses To Bcg Vaccinationmentioning
confidence: 96%
“…For example, suppression of lung T‐cell proliferation to purified protein derivative (PPD) occurred in co‐cultures of lung macrophages from M. tuberculosis ‐infected mice 25 . Previously, we have reported that alveolar macrophages (AMøs) as well as lung tissue macrophages (LMøs) obtained from BCG‐vaccinated guinea pigs suppressed the proliferation of lung T cells to PPD while peritoneal macrophages (PMøs) induced robust proliferation 26 . However, the effect of BCG vaccination on the responses of lung cells from M. tuberculosis ‐infected guinea pigs has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Lung infections, especially experimental paracoccidioidomycosis (PCMEx) [3][4][5], involve newly recruited CD11b + and CD23 + resident macrophages with potential immune disturbances for the host [6]. Several studies have implicated lung alveolar macrophages in the suppressive process of T-lymphocytes [7,8]. The mechanism by which pulmonary macrophages mediate the suppression of the T-lymphocytes proliferation in PCMEx is still unclear; however, it might involve soluble factors, either Th1/Th2 interleukins [9,10], CD23s [11], prostaglandins [12], regulatory T cells [13], antagonist of the IL receptors [14], accessory molecules, such as CD80 [15], CD86 [16], adhesion molecules [17][18][19][20] or genetic background of the host [21].…”
Section: Introductionmentioning
confidence: 99%